Structural investigation of crystalline host phosphor cadmium tellurite systems - Hussin, Rosli (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2009)
Generally, the luminescent properties of phosphors are strongly dependent on the crystal structure of the host materials. Finding a stable crystal structure, high physical and chemical stability of crystalline matrix is still a critical step to obtain rare-earth ions or transition metal ions-doped persistent phosphor with excellent properties. The glassceramic materials based on cadmium tellurite developed for stable host phosphor is reported in this paper. The structure of TeO2 and CdO-TeO2 system has been investigated by means of FT-Raman, Infrared (IR) spectroscopy and x-ray diffraction (XRD) spectroscopies. Cadmium tellurite system were prepared with the compositions of xCdO-(1-x)TeO2 with 0.1 ??x ? 0.5 in percent molar ratio, doped with 1% mol MnO2, using solid state method. The x-ray diffraction measurement results showed that the phase in the cadmium tellurite system matched quite well with the standard ICDD files, indicating that the phases present in this sample appeared to be a phase of ??-TeO4 trigional bipyramid (tbp), CdT O2O5 and CdTeO3. The Raman and Infrared spectra show that the structures are mainly builds by TeO4 (tbp) groups, TeO3+1 trigional pyramid (tp) and TeO3 (tp), while Cd2+ ions play as network modifiers. As addition concentration of CdO increases, TeO4 (tbp) groups progressively change polymerized framework structure in TeO4 (tbp) into TeO3+1 trigional pyramid (tp) and TeO3 (tp). On the contrary, the addition of 1 mol % MnO2 into the sample did not giving any effect on the structural of the final samples